Pengaruh Media Edutainment terhadap Self-Efficacy Siswi dalam Menghadapi Menarche Ditinjau dari Pengetahuan dan Sikap - Sari, Monika Novita; Andayani, Sri Astutik; Munir, Zainal (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2025)
Menarche is the first menstrual experience that often triggers anxiety, fear, and shame in adolescent girls, especially when there is a lack of adequate information. Low self-efficacy in facing menarche is often associated with insufficient knowledge and a lack of positive attitudes about menstruation. This study aims to analyze the influence of edutainment media on the self-efficacy of female students in facing menarche in terms of their knowledge and attitudes about menstruation. The research method used is a quasi-experimental approach with a pretest-posttest with control group design. A total of 60 students from SMP Negeri 3 Kota Probolinggo were divided into two groups, namely the intervention group and the control group, with 30 students in each. The intervention was provided in the form of menarche education using edutainment media. The results showed a significant increase in students’ self-efficacy after receiving education through edutainment media, with an Asymp.Sig value of 0.00 (p < 0.05), indicating that the alternative hypothesis (Ha) was accepted. These findings demonstrate that edutainment media is effective in enhancing students' self-efficacy regarding menarche by strengthening their knowledge and promoting positive attitudes toward menstruation. Reproductive health education using interactive approaches such as edutainment is recommended as an educational strategy in school environments.